Does job satisfaction mediate the effect of teamwork and organizational citizenship behavior on job performance? - Santi Riana Dewi; Deviyantoro Deviyantoro; Kamil Husain; Siti Safaria (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
In an increasingly competitive business situation, employee performance is something that is increasingly becoming the main concern of organizations. Therefore, this research aims to find a model for improving employee performance through increasing teamwork and organizational citizenship behavior with job satisfaction as an intervening variable. This study was carried out in Merak Banten at an agrochemical company by distributing questionnaires to 50 respondents representing production, maintenance, warehouse, laboratory, and general departments. This kind of research is known as explanatory research, and it uses hypothesis testing to explain the link between variables. The collected questionnaire data was then analyzed using SEM statistical methods and PLS analysis with SmartPLS 4 software. The analysis outcome showed that the job satisfaction variable had a direct effect on performance, teamwork had a direct or indirect effect on performance and organizational citizenship behavior had no direct or indirect effect. on performance. This research implies that companies are advised to increase the value of organizational citizenship behavior to increase job satisfaction and employee performance.